2021
DOI: 10.1038/s41598-021-97899-9
|View full text |Cite
|
Sign up to set email alerts
|

Tuber yield and water efficiency of early potato varieties (Solanum tuberosum L.) cultivated under various irrigation levels

Abstract: This study aims to determine the effects of differences in variety and irrigations levels on potato yield (appropriate humidity, temperature, shading the plants from the sun if necessary) on potato yield in greenhouse conditions. Functions of potato production with respect to water use were developed for five dates of measurements of plant growth, in relation to the various vegetation phases. On the basis of potato vegetation phases, the potato water demand was determined. An experiment was conducted using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…The results show that the yield decreases as the irrigation amount decreases, with the highest yield at 180 mm of irrigation at a 5-day irrigation cycle. These results are consistent with those of previous studies ( Lehmann and Finger, 2014 ; Li et al., 2022 ) where it has been shown that decreasing the irrigation decreased the potato yields, but one simulation study has shown that excessive irrigation resulted in lower yields following the water stress ( Jama-Rodzenska et al., 2021 ). Our second set of simulations of 15 scenarios with fixed irrigation quota and varying irrigation cycles showed that a 20 mm irrigation quota at a 5 -day irrigation cycle resulted in the highest tuber yield than all the other scenarios.…”
Section: Discussionsupporting
confidence: 92%
“…The results show that the yield decreases as the irrigation amount decreases, with the highest yield at 180 mm of irrigation at a 5-day irrigation cycle. These results are consistent with those of previous studies ( Lehmann and Finger, 2014 ; Li et al., 2022 ) where it has been shown that decreasing the irrigation decreased the potato yields, but one simulation study has shown that excessive irrigation resulted in lower yields following the water stress ( Jama-Rodzenska et al., 2021 ). Our second set of simulations of 15 scenarios with fixed irrigation quota and varying irrigation cycles showed that a 20 mm irrigation quota at a 5 -day irrigation cycle resulted in the highest tuber yield than all the other scenarios.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, to characterize the superiority of genotypes, it is important to consider their responses to the different environments (da Silva, 2020). Potato tuber yield losses in the absence of water can reach as much as 69% and also reduces the development of the aboveground part: leaf and stem biomass (Jama-Rodzenska et al, 2021). Yield under water stress has been and continues to be the main index of selection used in many breeding programs to improve the drought tolerance of crops (Petcu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%